Implementasi Metode Reward dan Punishment dalam Pembelajaran Ilmu Nahwu di Madrasah Ihya’ Ulumuddin - Novida Aprilina Nisa Fitri; Galang Jagat Pangestu (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
This study aims to determine how the success of the reward and punishment method in learning nahwu science at Madrasah Ihya' Ulumuddin Pondok Pesantren Lirboyo Unit Darussalam Kota Kediri. Reward method is everything that is given by the teacher in the form of appreciation that pleases the feelings of students because of the good results that have been achieved in the educational process. The punishment method is a means of education, in the form of alternative actions that are desired is the general benefit that is to realize students in the aspect of discipline. Nahwu is the rules that can recognize the particulars of Arabic words, both in terms of i'rab and bina'. The results showed that the reward method applied in Madrasah Ihya' Ulumuddin when the learning process occurs in madrasah is by speech, such as "Smart boy". Body movements, such as "Applause". The punishment method applied is an educational action that can lead students to success in achieving nahwu knowledge. The types of punishment given or applied at Madrasah Ihya' Ulumuddin include "Standing". Keywords: Reward Method; Punishment Method; Nahwu Science.